2017
DOI: 10.12688/wellcomeopenres.11985.1
|View full text |Cite
|
Sign up to set email alerts
|

Community-level antibiotic access and use (ABACUS) in low- and middle-income countries: Finding targets for social interventions to improve appropriate antimicrobial use – an observational multi-centre study

Abstract: In many low- and middle-income countries (LMICs), a poor link between antibiotic policies and practices exists. Numerous contextual factors may influence the degree of antibiotic access, appropriateness of antibiotic provision, and actual use in communities. Therefore, improving appropriateness of antibiotic use in different communities in LMICs probably requires interventions tailored to the setting of interest, accounting for cultural context. Here we present the ABACUS study (AntiBiotic ACcess and USe), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…An observational study was conducted using quantitative and qualitative methods to examine household factors which influence antibiotic use among community members in Ghana between January 2016 and July, 2018 (18). The study employed three consecutive approaches.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An observational study was conducted using quantitative and qualitative methods to examine household factors which influence antibiotic use among community members in Ghana between January 2016 and July, 2018 (18). The study employed three consecutive approaches.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size used for this study was 1,100 household. The detailed description and calculation of the sample size for this study has been reported in the published study protocol (18). In brief, from previous studies, it was expected that on average about 70% of antibiotic use will be classified as inappropriate.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…This qualitative exploratory cross-sectional study is one component in a larger multi-country research project ABACUS (Antibiotic Access And Use) [ 36 ] which assessed and compared community-based antibiotic access and use in Bangladesh, South Africa, Ghana, Vietnam, Thailand and Mozambique. http://www.indepth-network.org/projects/abacus .…”
Section: Methodsmentioning
confidence: 99%
“…Sampling and recruitment followed the ABACUS study protocol under the direction of the third author (HW) [ 36 ]. Fourth and fifth authors (WAK and AM respectively) were ABACUS study investigators in the Matlab site.…”
Section: Methodsmentioning
confidence: 99%